Exploring research capacity and capability in a local authority: qualitative insights from leaders and staff - James Woodall; Chloe Bracewell; Andrew Passey; Samantha Start; Jane South (BMC Public Health)
Abstract Background Local authorities in England are ideally placed to address the social determinants of health in the communities they serve. An evidence-led approach to developing programmes and policies to tackle determinants of health is critical to ensuring outcomes are attained and resources are used appropriately. Previous studies though suggest that local authorities do not always use evidence consistently in their decision-making processes. This paper seeks therefore to explore perceived research capability and capacity across one local authority in northern England to understand how research influences policy and practice. Methods A qualitative exploration of 29 leaders and managers across the local authority, representing the four directorates of the organisation, was obtained to gain an overall understanding of research capacity and capability. Data were analysed thematically with eight overarching thematic categories derived. Results The capacity and capability for research across the local authority directorates varied. Some participants described departments within directorates as being research active where research was part of their core business. Conversely, some departments were engaged in front-line service delivery where research was not prioritised. In these areas there was a disconnect between daily working practices and research. Staff in these departments generally lacked skills and training in research, whereas those in research active areas often had professional training where research was incorporated. There was rarely a shared definition of research by participants and ambiguity in what constituted research was common. The local authority was perceived to gather lots of data, but this was often used very functionally to fulfil reporting obligations. Curiosity to explore data was often minimised due to work pressures. Links from local authority staff to democratically elected officials varied and research and evidence was not always routinely presented. The majority of participants recognised that reforming ways of working and developing a clear training offer around research would be beneficial to addressing health outcomes. Conclusions Data demonstrated variance between research practice, partnerships and culture in departments where space for intellectual curiosity was tempered by service demands. There were exceptions to this, where departmental views of research were positive and leaders valued the research-informed culture.